AIMS AND OBJECTIVES OF TEACHING A FOREIGN LANGUAGE IN A NON-LINGUISTIC UNIVERSITY - Niyazova Minara Bakramovna , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research paper specifics of the manifestation of methodological and didactic principles of teaching are shown, and new methodological provisions are revealed regarding the ratio of intensive and traditional teaching methods, the ratio of lectures and practical classes. The allocation of stages of training is substantiated, taking into account the specifics of training in a technical university and the levels of formation of communicative competence, namely, the preparatory stage, professionally oriented and the stage of special training, and their specificity is shown. For the first time in teaching foreign languages at a non-linguistic university, the ratio of all types of speech activity for each stage has been determined.